Improvement of the Hydrogen-Release Features of Mg-Graphene Composite by Adding Nickel via Reactive Ball Milling - Choi, Eunho; Kwak, Young Jun; Song, Myoung Youp (Korean Journal of Metals and Materials, 2019)
The dehydrogenation rates of graphene-added Mg (named Mg-5graphene) were very low at 573 K and 593 K. Ni was added to increase the dehydrogenation rates of graphene-added Mg. Samples (designated as Mg-2.5Ni-2.5graphene) with a composition of 95 wt% Mg + 2.5 wt% Ni + 2.5 wt% graphene were prepared by milling in hydrogen (reactive ball milling). Mg-2.5Ni-2.5graphene had significantly higher initial hydrogenation and dehydrogenation rates and much greater amounts of hydrogen absorbed and released after 60 min, Ha (60 min) and Hd (60 min), than Mg-5graphene. The addition of Ni lowered the magnesium hydride decomposition temperature from 683 K to 581 K. The activation of Mg-2.5Ni-2.5graphene was finished after the second hydrogenation-dehydrogenation cycle (n=2). Mg-2.5Ni-2.5graphene had a very high efficient capacity of stored hydrogen (the amount of hydrogen absorbed after 60 min) higher than 7 wt% (7.07 wt% at 573 K in 12 bar H2 at n=1). At n=1, the quantities of hydrogen released by Mg-2.5Ni-2.5graphene were 0.26 wt% H after 2.5 min and 3.34 wt% H after 60 min at 573K in 1.0 bar H2. KCI Citation Count: 6